Evaluation of antihypertensive potential of Ficus carica fruit - Alamgeer; Shifa Iman; Hira Asif; Muhammad Saleem (Taylor & Francis Group, 2017)
Context: Ficus carica L. (Moraceae) fruit is said to possess cardiovascular activity and has been used empirically in traditional phytotherapies for the treatment of hypertension and various other cardiovascular diseases. Objective: This study investigated the antihypertensive and cardioinhibitory activity of the aqueous-methanol extract of F. carica fruit in rats. Materials and methods: Extract in 250, 500 and 1000 mg/kg doses (p.o.) were administered to normotensive Sprague Dawley rats and blood pressure was measured using non-invasive technique. Hypertension was induced in rats by oral administration of 10% glucose for 3 weeks. Hypotensive effect of extract (1000 mg/kg p.o) was studied in normotensive and glucose-treated hypertensive rats. Langendorff's isolated heart technique was used to assess the effect of crude extract on force of contraction and heart rate. In addition, antioxidant potential, TPC, TFC were also assessed by DPPH free radical scavenging activity, Folin-Ciocalteu reagent and AlCl3 assay, respectively. Furthermore, phenolic compounds were analyzed using HPLC-DAD technique. Results and discussion: The 1000 mg/kg dose decreased blood pressure significantly in normotensive and glucose-treated hypertensive rats. The isolated heart study showed that the extract produced negative inotropic and chronotropic effects but it failed to block the stimulatory effect of both adrenaline and CaCl2. HPLC studies on the F. carica extract indicated the presence of quercetin, gallic acid, caffeic acid, vanillic acid, syringic acid, coumaric acid and chromotropic acid. Conclusions: This study demonstrated that aqueous methanol extract of F. carica fruit exerted hypotensive and antihypertensive effects in glucose-induced hypertensive rats.